2019
DOI: 10.3892/ol.2019.11038
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and molecular characteristics of abdominal desmoid tumors in the Chinese population: A single‑center report of 15�cases

Abstract: Desmoid tumors (DTs), derived from the abdomen, are a type of rare and aggressive borderline tumor exhibiting high recurrence and malignant potential. The aim of the present study was to investigate the clinicopathological and molecular characteristics of abdominal DT in a Chinese population and to provide clues for selecting the optimal treatment strategy for different types of abdominal DT. The clinicopathological data of 15 consecutive patients with DT was collected. Matched fresh-frozen tumor tissues and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Two patients in our cohort had pilomatrixomas, one had a VUS in POLD1 gene and the other one had an APC pathogenic variant in the germline. In addition, some soft tissue neoplasms have been described in adult patients with MUTYH pathogenic variants in the germline ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two patients in our cohort had pilomatrixomas, one had a VUS in POLD1 gene and the other one had an APC pathogenic variant in the germline. In addition, some soft tissue neoplasms have been described in adult patients with MUTYH pathogenic variants in the germline ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 18 Wang et al analyzed 15 DT patients and proposed that FAP patients with a history of abdominal surgery were more likely to develop abdominal DT and had a worse prognosis. 39 Ge et al analyzed the genotypes of FAP-associated DT and concluded that all FAP patients, except those with APC gene variants in the 5′ to 495 range, should consider the risk of postoperative DT. Among them, patients with 3′ 1062 and 3′ 1399 codon variants had a significantly higher risk of DT.…”
Section: Adenomatous Polyposis Syndromementioning
confidence: 99%